La vie monastique aujourd'hui: du retrait à l'accueil du monde? - Poswick, R.-Ferdinand (Nouvelle revue théologique, 2018)
Here is a weighty book both in volume and density! The author delivers to us the interpretation which she gives to the enquiries which she conducted in the Benedictine and Cistercian monasteries of French speaking Europe to try to grasp the developments of these communities since their foundation or re-foundation at the end of the 19th century! (...)